2014
DOI: 10.1186/1471-2474-15-175
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected angular or rotational deformity after corrective osteotomy

Abstract: BackgroundCodman’s paradox reveals a misunderstanding of geometry in orthopedic practice. Physicians often encounter situations that cannot be understood intuitively during orthopedic interventions such as corrective osteotomy. Occasionally, unexpected angular or rotational deformity occurs during surgery.This study aimed to draw the attention of orthopedic surgeons toward the concepts of orientation and rotation and demonstrate the potential for unexpected deformity after orthopedic interventions. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Unfortunately, while successful in treating antetorsion, rotational osteotomy carries a high risk of change of axis alignment. 16 , 20 Paley and Herzenberg 22 showed a way to address the frontal axis combined with torsion for the correction of deformities. Their mathematical approach is complex and contains information that can be adapted to different tubular bones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, while successful in treating antetorsion, rotational osteotomy carries a high risk of change of axis alignment. 16 , 20 Paley and Herzenberg 22 showed a way to address the frontal axis combined with torsion for the correction of deformities. Their mathematical approach is complex and contains information that can be adapted to different tubular bones.…”
Section: Discussionmentioning
confidence: 99%
“…Orientations, plane views, and anatomic references due to rotation are elementary and not easily transferable into the operating room. 16 With regard to derotational osteotomy in cases of patellofemoral instability, unintended axis malalignment such as postoperative increased valgus contradicts the initial purpose of treating patellofemoral malalignment. The presence of valgus malalignment is known to be an additional risk factor in patellofemoral instability cases, independent from maltorsion.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al showed in several computer simulations that unexpected angular or rotational deformity can occur during rotational osteotomies [ 16 ]. They stated that femoral antecurvation and femoral bowing can affect the alignment of the lower leg and that osteotomy on the anatomical shaft, proximal or distal, influences mechanical axis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased valgus alignment could lead to increased lateral facet pressure and increased medial retinaculum strain [ 12 14 ]. In the clinical experience and with regards to previous publications, derotational osteotomies may result in unplanned frontal malalignment; thus, unintended valgus producing effects should be avoided strictly [ 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Femoral rotational deformities with excessive antetorsion or retrotorsion are frequently seen in patients with femoroacetabular impingement [1,2], hip dysplasia [3,4] or patellofemoral instability [5,6]. Established treatment options are free-hand subtrochanteric or supracondylar femoral rotational osteotomies [7][8][9], bearing the risk of unintended changes in mechanical leg axis [10,11]. Furthermore, a computer model study by Nelitz M et al [12] showed a tendency to varus angulation in proximal-and a tendency to valgus angulation in distal femoral external-rotational osteotomies.…”
Section: Introductionmentioning
confidence: 99%